Fatores de risco cardiovascular em diferentes níveis socioeconômicos de Servidores Públicos da Universidade Agostinho Neto, Luanda, Angola - Capingana, Daniel Pires (2012)
Background: Cardiovascular diseases are the leading cause of death in the majority of developed and developing countries. African countries are currently facing an increase in both cardiovascular and transmitted diseases. In addition, cardiovascular risk varies among different socioeconomic groups. Objective: Characterize the modifiable cardiovascular risk factors in different socioeconomic status of public-sector workers of the Agostinho Neto University in Luanda, Angola, and to estimate the risk of developing coronary artery disease in 10 years according to the Framingham algorithm. Methods: We employed a cross-sectional study comprising 42.2% (n = 615) of the public-sector workers at Agostinho Neto University, 48% (n = 294) male and 52% (n = 321) female, with ages between 20 and 72 years and from various socioeconomic groups. The study was conducted from February 2009 to December 2010. Results: The means of body mass index (27.1±5.8 Kg/m2 ), and waist circumference (83.9±13.5 cm) were higher (P<0,05) in women than men, whilst the mean of the Sokolow-Lyon index was higher in men (31.1±8.9 mm) than in women (23.2±7.2 mm). The prevalence rates of cardiovascular risk factors were as follows: hypertension, 45.2% (men 46.3%, women 44.2%); hypercholesterolemia, 11.1% (men 10.5%, women 11.5%); low high-density lipoprotein (HDL) cholesterol, 50.1% (men 36.9%, women 62.3%; P < 0.05); smoking, 7.2% (men 10.2%, women 4.4%; P < 0.05); diabetes, 5.7 % (men 5.5%, women 5.9%); obesity, 19.6% (men 9.2%, women 29%; P < 0.05); and left ventricular hypertrophy, 20% (men 32.0%, women 9%; P < 0.05). The waist circumference and age were predictors of change in systolic blood pressure in subjects without cardiovascular risk factor. The lower socioeconomic class had higher (P <0.05) prevalence of hypertension (55.8% vs 45.1%), smoking (14.3% vs 2.6%) and LVH (30.5 vs 14%, 4%) than the upper socioeconomic class. One risk factor was present in 27.7% of the sample; 15.2% had two risk factors, and 31.4% had three or more risk factors. Among the individuals with low socioeconomic status, 41% had three or more risk factors. 58.3% of individuals at high risk had low education, and the lower socioeconomic class had the highest proportion of high risk (23.6%, P <0.05) than the upper socioeconomic class (10.1%). Conclusions: The data show the high prevalence of multiple risk factors of cardiovascular disease in active public-sector workers in Angola. The low socioeconomic status had more harm to cardiovascular health, because had higher prevalence of hypertension, smoking, and left ventricular hypertrophy. The coexistence of multiple risk factors in these workers indicates the need to intensify efforts for prevention and early identification of risk factors, especially the lower income segments.